The chaos agent [large type] - Greaney, Mark (Greaney, Mark. Gray Man novel., 2024)
"Artificial intelligence leads to shockingly real danger for the Gray Man in this latest entry in the #1 New York Times bestselling series. A car accident in Japan. A drowning in Seoul. A home invasion in Boston. Someone is killing the world's leading experts on robotics and artificial intelligence. Is it a tech company trying to eliminate the competition or is it something even more sinister? After all, artificial intelligence may be the deadliest battlefield gamechanger since the creation of gunpowder. The first nation to field weapons that can act at the speed of computer commands will rule the battlefield. It's an irresistible lure for most, but not for the Gray Man. His quest for a quiet life has led him to Central America where he and his lover, Zoya Zakharova, have assumed new identities. With a list of enemies that includes billionaires, terrorists, and governments, they need to keep a low profile, but the world's deadliest assassin can't expect to hide out forever. Eventually, they're tracked down and offered a job by an old acquaintance of Zoya's. He needs their help extracting a Russian scientist who is on the kill list. They reject the offer, but just being seen with him is enough to put assassins on their trail. Now, they're back on the run, but no matter which way they turn, it's clear that whoever's tracking them is always going to be one step ahead. Since flight's no longer possible, fight is the only option left, and no one fights dirtier than the Gray Man"--